Coupling of autoionizing states by a chirped laser pulse. Issue 8 (January 2020) - Žitnik, M; Mihelič, A; Bučar, K; Hrast, M; Barba, Ž; Krušič, Š; Ribič, P Rebernik; Urbančič, J; Ressel, B; Stupar, M; Poletto, L; Coreno, M; et al.
Synopsis: We have observed the autoionization of the laser-coupled 2s2 p 1 P o and 2 p 2 1 S e resonances in helium. The ions were collected while varying the frequency and delay of the extreme-ultraviolet (EUV) excitation pulse with respect to the linearly chirped visible (VIS) laser pulse. From the measured frequency-delay map the Autler-Townes splitting, the EUV-VIS cross-correlation and the linear chirp parameter were extracted.